Analyzing the questioning style used in Surah Al-Ahqaf: A rhetorical and analytical study with implications for teaching Arabic. - Alfian mubarok; Alip Piati (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2025)
The interrogative methode is an important Arabic grammar rule that must be taken into account when determining the meanings of the Quran or the Arabic language in order to avoid misunderstandings. Accordingly, the researcher attempted to write a research paper on this topic. This study aims to uncover the secrets of the interrogative style tools and their rhetorical purposes in Surat Al-Ahqof. Primary sources include books on rhetoric, including: Al-Balagha Al-Wadiha, Al-Idah fi Ilm Al-Balagha, and Jawahir Al-Balagha. Secondary sources include: Tafsir Al-Tahrir wa Al-Tanwir, Tafsir Al-Munir fi Al-Aqeedah wa Al-Sharia, and several dictionaries, including the Dictionary of Contemporary Arabic Language, the Intermediate Dictionary, and Lisan Al-Arab.  The type of research used in this research is qualitative research, and the method followed by the researcher to complete this research is the descriptive analytical method that relies on the documents related to this topic. The study concluded that Surah Al-Ahqaf has 9 verses and contains 12 tools that use the interrogative style with various tools, namely "man" in two places for different purposes, including: what indicates denial, negation, and the literal meaning. "Al-Hamza" is used in six places for different purposes, including: rebuke, denial, and confirmation. The report states that "umm" is used in two places for the purpose of a piece, meaning "rather" and denial. "ma" is a single tool for the purpose of denial, and the last "hal" is a single tool for the purpose of denial. Consequently, the results of this study can be used in teaching ArabicKeywords:  Introgative method, Surat Al-ahqaf,  teaching Arabic